Implementation of the Quiz-Quiz Trade Learning Model to Improve Higher Order Thinking Skills (HOTS) and History Learning Outcomes of Students at SMA Negeri 22 Maluku Tengah - Lesnussa, Olin Catrin; Patotnem, Chrismas Perty; Salenussa, Ona Amelia; Pusparani, Rina; Dokolamo, Hamid (Riwayat: Educational Journal of History and Humanities, 2022)
This study aims to improve students' Higher Order Thinking Skills (HOTS) and history learning outcomes through the implementation of the Quiz-Quiz Trade learning model at SMA 22 Maluku Tengah. The method used is Classroom Action Research (CAR), involving 32 students of class X IPS as research subjects. The research was conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The results showed a significant improvement in both students history learning outcomes and their HOTS abilities. The initial test showed a classical completeness of only 25%, which increased to 68.75% in the first cycle and reached 93.75% in the second cycle. Students HOTS also improved from 70% in the first cycle to 87.5% in the second cycle, categorized as very good. Therefore, it can be concluded that the Quiz-Quiz Trade learning model is effective in enhancing higher-order thinking skills and history learning outcomes of students at SMA 22 Maluku Tengah